Hearing sensitivity and amplitude coding in bats are differentially shaped by echolocation calls and social calls - Lattenkamp, Ella; Nagy, Martina; Drexl, Markus; Vernes, Sonja; Wiegrebe, Lutz; Knörnschild, Mirjam (Dryad, 2020)
Differences in auditory perception between species are influenced by
phylogenetic origin and the perceptual challenges imposed by the natural
environment, e.g. detecting prey- or predator-generated sounds and
communication signals. Bats are well suited for comparative studies on
auditory perception since they predominantly rely on echolocation to
perceive the world, while their social calls and most environmental sounds
have low frequencies. We tested if hearing sensitivity and stimulus level
coding in bats differ between high and low frequency ranges by measuring
auditory brainstem responses (ABRs) of 86 bats belonging to 11 species. In
most species, auditory sensitivity was equally good at both high and low
frequency ranges, while amplitude was more finely coded for higher
frequency ranges. Additionally, we conducted a phylogenetic comparative
analysis by combining our ABR data with published data on 27 species.
Species-specific peaks in hearing sensitivity correlated with peak
frequencies of echolocation calls and pup isolation calls, suggesting that
changes in hearing sensitivity evolved in response to frequency changes of
echolocation and social calls. Overall, our study provides the most
comprehensive comparative assessment of bat hearing capacities to date and
highlights the evolutionary pressures acting on their sensory perception.
Keywords: hearing threshold; audiogram; Auditory Brainstem Responses; dynamic range; sensory system evolution; amplitude coding